Pembrolizumab plus axitinib combination and the paradigm change in the treatment of advanced renal cell carcinoma - Spisarová, Martina; Melichar, Bohuslav; Vitásková, Denisa; Študentová, Hana (Future oncology (London, England), 2021)
Sequential administration of single targeted agents has been challenged as the dominant treatment paradigm in patients with metastatic renal cell carcinoma by improved outcomes obtained with combination regimens based on immune checkpoint inhibitors. Most patients treated with sequential monotherapy eventually develop drug resistance and succumb to progressive disease, leading to the search for therapies that would overcome drug resistance and result in a more durable treatment response. Improved outcomes have been demonstrated in Phase III trials in comparison with sunitinib for the combinations of axitinib plus pembrolizumab, axitinib plus avelumab, bevacizumab plus atezolizumab and ipilimumab plus nivolumab. A statistically significant improvement of both progression-free and overall survival has been demonstrated for the axitinib plus pembrolizumab combination.
Keywords: karcinom z renálních buněk; doba přežití bez progrese choroby; multiple tyrosine kinase inhibitors; míra přežití; pembrolizumab; immune checkpoint inhibitors; Humans; Clinical Trials, Phase III as Topic; Antibodies, Monoclonal, Humanized; nádory ledvin; lidé; Immune Checkpoint Inhibitors; Safety; Kidney Neoplasms; Axitinib; inhibitory kontrolních bodů; axitinib; Antineoplastic Combined Chemotherapy Protocols; Protein Kinase Inhibitors; bezpečnost; klinické zkoušky, fáze III jako téma; Progression-Free Survival; protokoly protinádorové kombinované chemoterapie; immunotherapy; metastatic renal cell carcinoma; Survival Rate; inhibitory proteinkinas; humanizované monoklonální protilátky; Carcinoma, Renal Cell